KEPEMIMPINAN PENDIDIKAN BERBASIS INOVASI PADA ERA ARTIFICIAL INTELLIGENCE - Merriam Modeong; Herry Sumual; Davidsen Mapaliey; Firando S. Kindangen; Telly Tangkere (Jurnal Manajemen Pendidikan, 2026)
This study was conducted to examine and analyze the forms of innovation-based educational leadership in the era of Artificial Intelligence (AI). Contemporary leaders are required to adapt and transform their leadership approaches in response to technological advancements within the educational institutions they lead. The method employed in this study was a systematic literature review through the examination of various scholarly sources, followed by an analysis of innovative leadership, digital transformation in education, and the implementation of Artificial Intelligence (AI) in educational management. The findings indicate that innovation-based educational leadership in the AI era requires leaders to possess five main competencies: strong digital literacy skills, adaptive capabilities, a growth mindset, cross-sector collaboration skills, and data-driven decision-making abilities. The leadership model developed in this study integrates transformational, distributive, and technological leadership approaches to create an educational ecosystem that is responsive to various changes. Educational leaders are expected to foster a culture of innovation by utilizing technology, particularly AI, as a supporting medium for decision-making processes and the improvement of learning quality. The implications of this study provide a conceptual framework for educational leaders in designing adaptive and innovative leadership strategies in the AI era.